2018
DOI: 10.1007/s10140-018-1642-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparity in academic emergency radiology

Frank Battaglia,
Samad Shah,
Sabeena Jalal
et al.

Abstract: This study provides further evidence that gender disparity persists in emergency radiology, with women achieving less upward academic career mobility than men, despite better academic productivity in the earlier stages of their careers. The academic productivity of emergency radiologists at the rank of assistant professor is significantly higher for women than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…In evaluating demographic data in this study, a sobering observation concerns the lack of diversity of current VCEs of EM in the United States. Findings are congruent with other studies that highlight gender disparities in medicine . According to the 2013–2014 AAMC report, The State of Women in Academic Medicine , only 15% of department chairs and 16% of deans are women, with only a marginal increase observed over the past decade .…”
Section: Discussionsupporting
confidence: 86%
“…In evaluating demographic data in this study, a sobering observation concerns the lack of diversity of current VCEs of EM in the United States. Findings are congruent with other studies that highlight gender disparities in medicine . According to the 2013–2014 AAMC report, The State of Women in Academic Medicine , only 15% of department chairs and 16% of deans are women, with only a marginal increase observed over the past decade .…”
Section: Discussionsupporting
confidence: 86%
“…Fifty-two articles (85.2%) fulfilled at least four of the quality appraisal criteria [7,11,12,71,72,75,76,[78][79][80][81][82]84,[86][87][88][89][91][92][93][94][95][96][97][121][122][123][124][125][126][127] (see Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Our methodology has been validated in several recent publications. [1][2][3][4][5]9] We obtained a list of orthopedic programs to gather the academic faculty members of each orthopedic department. The Canadian Resident Matching Service (CaRMS) website enlists a total of 17 university hospitals that offer orthopedic training programs.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that most surgical specialties are male-dominated. Previous investigations in radiology were able to quantify the disparity and provide strong evidence to suggest that research productivity was a major factor for the ongoing disparity [1][2][3]. These studies found that women were a minority in the academic practice, were at the lower rungs of academic ranks, were disproportionally represented in leadership positions, had lower research productivity and lower H-index scores when compared to men.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation